Got milk? Not in public! - Wolf Jacqueline H (BMC, 2008)
Abstract The American focus on the sexual purpose of breasts, rather than the physiological function of breasts, has serious public health consequences. Discomfort with breastfeeding in public lowers breastfeeding rates, which in turn negatively affects women's and children's short- and long-term health.